Developing online quiz with a 3D animation pipeline to enhance student engagement - Devaga Betayoka; Henry Praherdhiono; Agus Wedi (Inovasi Kurikulum, 2026)
Online quiz media should be developed to help students focus on learning activities. In addition, online quiz media can encourage students to participate actively in teacher-administered evaluations. This study aims to increase student engagement in learning activities. This development method employs the ADDIE model to design online quiz media using Kahoot! The results of this study indicate that students prefer practical learning. Online quiz media were developed to increase student engagement and understanding of theoretical concepts through varied learning activities. Using online quiz platforms such as Kahoot! can help students understand the learning materials and increase their motivation to learn. Other findings also show that students become more involved in the learning process. Furthermore, this learning media is equipped with animations and bright colors to prevent boredom during quiz work. In addition, this media can facilitate two-way communication between teachers and students, thereby creating a positive classroom atmosphere.   Abstrak Media kuis online perlu dikembangkan karena dapat membantu fokus murid dalam kegiatan pembelajaran. Selain itu, media kuis online dapat membuat murid aktif mengikuti kuis sebagai bentuk evaluasi yang diberikan oleh guru. Penelitian ini bertujuan untuk meningkatkan keterlibatan murid dalam kegiatan pembelajaran. Metode pengembangan ini menggunakan ADDIE dalam mengembangkan media kuis online berbasis Kahoot!. Hasil penelitian ini menunjukkan murid lebih menyukai pembelajaran praktik. Media kuis online dikembangkan untuk meningkatkan keterlibatan dan pemahaman murid terhadap pembelajaran teori sebagai variasi dalam kegiatan pembelajaran. Melalui media kuis online berbasis Kahoot! dapat membantu murid dalam memahami materi pembelajaran dan meningkatkan motivasi mereka dalam belajar. Temuan lain juga menunjukkan bahwa murid menjadi lebih banyak terlibat pada proses pembelajaran. Lebih lanjut, media pembelajaran ini dilengkapi dengan animasi dan warna yang cerah menyebabkan para murid tidak merasa bosan ketika mengerjakan kuis. Selain itu, media ini dapat menyebabkan berlangsungnya komunikasi dua arah antara guru dan murid, sehingga tercipta suasana kelas yang menyenangkan. Kata Kunci: evaluasi pembelajaran; keterlibatan murid; media kuis online